Enhancement of microwave power sensor measurement with adaptors - Qiu, Tie (2014)
Calibration is important in microwave power sensor measurement, since it can improve the overall accuracy of the measurement. A calibration factor is used as a correction factor; it describes both the effective efficiency and reflection coefficient of the power sensor. Generally, the calibration factor will be used in the calibration transfer from a reference standard to the device under test. And the direct comparison transfer technique is the simplest and most evident method to achieve the calibration of power sensors by using calibration transfer. Nowadays, for further developments of the direct comparison technique, different adaptors (attenuators) could be used in some implementations. Therefore, their effects should be investigated since they can introduce additional measurement uncertainties.